1993
DOI: 10.1115/1.2910691
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement From a Vertical, Isothermal Channel Generated by the Chimney Effect

Abstract: A numerical and experimental investigation of free convection from vertical, isothermal, parallel-walled channels has been undertaken to explore the heat transfer enhancement obtained by adding adiabatic extensions of various sizes and shapes. Investigations were carried out for air (Pr= 0.7) over a wide range of wall heating conditions. In all cases, the adiabatic extensions were able to increase heat transfer. The increase varied from 2.5 at low Ra* to 1.5 at high Ra*. The experimental and numerical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…The reservoirs are employed in order to simulate thermal and fluid dynamic behaviors far away from the inflow and outflow regions. The geometry studied in this numerical investigation is important in different applications, such as in electronic cooling [9,[11][12][13][14]18,23,24,27] and in building ventilation and houses solar components [8,10,11,16,17,[31][32][33]. The main differences between the present investigation and the study in reference [19] is the considered geometrical configuration.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…The reservoirs are employed in order to simulate thermal and fluid dynamic behaviors far away from the inflow and outflow regions. The geometry studied in this numerical investigation is important in different applications, such as in electronic cooling [9,[11][12][13][14]18,23,24,27] and in building ventilation and houses solar components [8,10,11,16,17,[31][32][33]. The main differences between the present investigation and the study in reference [19] is the considered geometrical configuration.…”
Section: Introductionmentioning
confidence: 84%
“…On the top of the channel there is a chimney made of two adiabatic parallel and vertical plates; their height is L-L h and the distance between them is B. An enlarged computational domain has been chosen as employed and suggested in [6,23,24]. It is made up of the previously described geometry and of two reservoirs of height L X and width L Y , which are placed upstream the channel and downstream the chimney.…”
Section: Analysis and Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2.5 times higher heat transfer rate was numerically obtained. For the case of square channel, Straatman et al [13] systemically examined the chimney effect in a single heated parallel-walled channel covered with an adiabatic extension. They found that the expanded chimney (having a longer length) offered an enhancement ranging from 30 to 250 percent.…”
Section: Introductionmentioning
confidence: 99%